2014
DOI: 10.1074/jbc.m113.514414
|View full text |Cite
|
Sign up to set email alerts
|

Electric Stimulus Opens Intercellular Spaces in Skin

Abstract: Background: Although skin is a tight barrier, transdermal liposome delivery is achievable by faint electric stimulus (ES). Results: ES caused rigid nanoparticle penetration into the epidermis, and induced connexin 43 phosphorylation, actin fiber depolymerization and Ca 2ϩ -influx. Conclusion: Our data indicate that ES opens epidermis intercellular spaces via intracellular signaling activation. Significance: Skin barrier permeability could be controlled by ES via changes in cutaneous physiological properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…7) Iontophoresis is an effective technology for transdermal delivery of nanoparticles, such as liposomes, using faint electricity. 8) We found that faint electric treatment opened intercellular junctions in the skin. 8) Further, liposomes were shown to penetrate to deep regions of the skin through the intercellular space by iontophoresis because of the flexible structure of the lipid vesicles.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…7) Iontophoresis is an effective technology for transdermal delivery of nanoparticles, such as liposomes, using faint electricity. 8) We found that faint electric treatment opened intercellular junctions in the skin. 8) Further, liposomes were shown to penetrate to deep regions of the skin through the intercellular space by iontophoresis because of the flexible structure of the lipid vesicles.…”
mentioning
confidence: 83%
“…8) We found that faint electric treatment opened intercellular junctions in the skin. 8) Further, liposomes were shown to penetrate to deep regions of the skin through the intercellular space by iontophoresis because of the flexible structure of the lipid vesicles. 8) On the other hand, polymerbased nanoparticles accumulated in the epidermis due to their rigid structures.…”
mentioning
confidence: 83%
See 3 more Smart Citations